Portofolio Digital Google Sites dalam Pembelajaran Ilmu Pengetahuan Sosial di Madrasah Ibtidaiyah Swasta - Yusnaldi, Eka; Putri, Fia Alifah; Adesti, Anita; Jalal, Muhaiminah; Matvayodha, Gupo (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2023)
Google sites-based digital portfolios have been developed by the Tanoto Foundation through portfolios, lesson plans (RPP), learning media, student worksheets (LKPD), summative assessments, and learning practices. The purpose of this study is to explain the flexibility of using Google Sites digital portfolios in student academic review through social studies learning on ASEAN material. With a descriptive qualitative approach and observation, interview, and documentation techniques, it is hoped that the research will be accurate in its presentation. This research is located at MI Al Munawarah Jambi which is a partner of the Tanoto Foundation. The results of this study indicate that with the use of digital portfolios and Google Sites madrasah head can review the teachers in carrying out learning tasks, a teacher can review the academic development of students and parents can review the academic development of their children through Google Sites-based learning. In learning social studies ASEAN material through digital portfolios, students can prepare themselves to learn the upcoming material, if the student's score is low then the student can repeat the material or summative assessment LKPD at home.